A MULTI-STAGE SUPPLY CHAIN MODEL TO DETERMINE OPTIMAL DISTRIBUTION CENTER STRATEGY - Ozesenli, Ozhan Nuri; Demirel, Tufan (YILDIZ TECHNICAL UNIV, 2011)
Distribution center (DC) strategies are one of the most important strategic decisions in the optimization of supply chain networks (SCN). In this paper, a multi-stage, multi-period, multi-product SCN model, which includes procurement, production and distribution is developed. The main contribution of this study is to introduce a model, which enables to change the number, locations, scales and capacity levels of DCs to optimize total supply chain (SC) cost. The SCN is modeled as a mixed integer linear problem to satisfy estimated demand with minimum fixed and variable cost entities, which are subject to capacity of suppliers and production facilities with locations and scales of DCs. Suggested model is applied to SCN of a multinational Fast Moving Consumer Goods Company (FMCG) to examine the performance of the model in real world cases. Three different strategies for DCs are implemented and run under 36 different scenarios via an optimization package, Insight's SAILS (R), with real data. The performance of strategies under different scenarios is compared. It is found that SML approach performs better than other strategies under all scenarios.
Keywords: Supply chain management; mixed integer programming; network design; DESIGN; Engineering